1992
DOI: 10.1073/pnas.89.19.9107
|View full text |Cite
|
Sign up to set email alerts
|

Fc epsilon RI-mediated tyrosine phosphorylation and activation of the 72-kDa protein-tyrosine kinase, PTK72, in RBL-2H3 rat tumor mast cells.

Abstract: In RBL-2H3 rat tumor mast cells, cross- The RBL-2H3 rat tumor mast cell line has proven to be an excellent experimental model for studies of receptormediated cell activation. Antigen-mediated cross-linking of the high-affinity IgE receptor, FceRI, on these cells leads to Ca2+ influx, phosphatidylinositol turnover, release of serotonin and other substances from granules, polymerization of actin, and transformation of the cell surface from a microvillous to a lamellar architecture (reviewed in refs. 1 and 2). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(121 citation statements)
references
References 23 publications
3
118
0
Order By: Relevance
“…Engagement of the tetrameric (~fl~'2) FceRI receptors mediates the activation of the non-receptor tyrosine kinases Lyn and Syk [1][2][3][4][5][6]. The activation of these kinases leads to the phosphorylation of various substrates including the fl and ?'…”
Section: Introductionmentioning
confidence: 99%
“…Engagement of the tetrameric (~fl~'2) FceRI receptors mediates the activation of the non-receptor tyrosine kinases Lyn and Syk [1][2][3][4][5][6]. The activation of these kinases leads to the phosphorylation of various substrates including the fl and ?'…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to determine which pathways are primarily affected, we first analyzed tyrosine phosphorylation of Syk. This kinase becomes rapidly phosphorylated in Thy-1- [12], TEC-21-[8] or Fc 4 RI- [13] activated RBL cells, and has already been shown to exhibit an increased tyrosine phosphorylation in latrunculinpretreated and Fc 4 RI-activated cells [2]. Immunoblotting analysis showed that phosphorylation of Syk was slightly increased by latrunculin alone, i.e.…”
Section: Early Activation Pathwaysmentioning
confidence: 99%
“…In addition to being used as immunosuppressants, mTORC1 inhibitors are evaluated as therapeutic agents in various types of cancer, 5,6 with high efficacy already documented in renal cell carcinoma. 13 Syk is a protein tyrosine kinase expressed in B lymphocytes, 14 monocytes/macrophages, 15 mast cells, 16 and other cell types. Syk has been found to be involved in signal transduction through several types of receptors including the antigen B-cell receptor 17 and at least three different receptors for the Fc component of immunoglobulins G and E. 14 -16,18 -20 A recent report suggests that Syk may be involved in mTORC1 activation in a follicular and possibly other types of B-cell lymphoma.…”
mentioning
confidence: 99%